2010
DOI: 10.1371/journal.pone.0010068
|View full text |Cite
|
Sign up to set email alerts
|

“Positive” Results Increase Down the Hierarchy of the Sciences

Abstract: The hypothesis of a Hierarchy of the Sciences with physical sciences at the top, social sciences at the bottom, and biological sciences in-between is nearly 200 years old. This order is intuitive and reflected in many features of academic life, but whether it reflects the “hardness” of scientific research—i.e., the extent to which research questions and results are determined by data and theories as opposed to non-cognitive factors—is controversial. This study analysed 2434 papers published in all disciplines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
605
10
25

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 652 publications
(662 citation statements)
references
References 62 publications
22
605
10
25
Order By: Relevance
“…This is intuitively expected given the widespread practice of null hypothesis significance testing (NHST). Fanelli (2010) reports shocking metrics of this phenomenon. He analyzed 2434 papers from all disciplines that report hypothesis testing, and shows that as we go down in "the hierarchy of sciences" (i.e., a hypothesized hierarchy that Fanelli traces back to Comte, in which physics is at the top and the behavioral sciences at the bottom-of course, we need not agree that there is such a hierarchy), published results tend to be more significant than non-significant.…”
Section: Publication Of Positive Results Onlymentioning
confidence: 99%
“…This is intuitively expected given the widespread practice of null hypothesis significance testing (NHST). Fanelli (2010) reports shocking metrics of this phenomenon. He analyzed 2434 papers from all disciplines that report hypothesis testing, and shows that as we go down in "the hierarchy of sciences" (i.e., a hypothesized hierarchy that Fanelli traces back to Comte, in which physics is at the top and the behavioral sciences at the bottom-of course, we need not agree that there is such a hierarchy), published results tend to be more significant than non-significant.…”
Section: Publication Of Positive Results Onlymentioning
confidence: 99%
“…However, it is yet unknown to what extent bias patterns and postulated risk factors are generalizable phenomena that threaten all scientific fields in similar ways and whether studies documenting such problems are reproducible (5)(6)(7). Indeed, evidence suggests that biases may be heterogeneously distributed in the literature.…”
mentioning
confidence: 99%
“…For example, medical journals have seen an increase in the percentage of retracted articles (Steen, 2011a(Steen, , 2011b, and there is the concern that a vast number of published findings may be false (Ioannidis, 2005). However, a recent comparison of different scientific disciplines suggested that the bias is stronger in psychology than in some of the older and harder scientific disciplines at the top of a hierarchy of sciences (Fanelli, 2010).…”
mentioning
confidence: 99%